Long-term trends in cancer incidence and mortality among U.S. children and adolescents: a SEER database analysis from 1975 to 2018 - Tang, Xiao-Wei; Jiang, Jiao; Huang, Shu; Shi, Xiao-Min; Xu, Huan; Xu, Jia; Peng, Jie-Yu; Zhang, Wei; Shi, Lei; Zhong, Xiao-Lin; Kang, Min; Lü, Mu-Han (Frontiers in Pediatrics, 2024)
Background: Childhood and adolescent cancer represent a significant health burden in the United States.Current and precise epidemiological data are crucial to develop effective cancer control plans and ultimately reduce the burden of childhood and adolescent cancer.Methods: We analyzed data obtained from cancer registries in the National Cancer Institute's Surveillance, Epidemiology, and End Results Program. Age-standardized incidence and death rates, assessed using joinpoint analysis, were quantified as annual percentage changes (APC) and average percentage changes (AAPC). Results: The overall cancer incidence rate in 2008-2018 was 187.9 per 1000000 persons. Cancer incidence rates demonstrated a sustained upward trend, with an APC of 0.8 from 1975 to 2018. Incidence rates during 2008-2018 remained stable among non-Hispanic Black children but increased among other racial and ethnic groups. Leukemias, central nervous system tumors, and lymphomas were the most common cancer groups for patients aged 0-19 years. Cancer death rates decreased among children (AAPC, -1.3 [95% CI, -1.5 to -1.1]) during 2009-2019, while were stable among adolescents during that period.Conclusions: In this study, we analyzed cancer incidence and mortality rates and trends in children aged 0 to 19 years in the United States. Our findings revealed an overall increase in cancer incidence rates among children and adolescents, accompanied by a decline in cancer mortality rates over time. These rates and trends varied by age, sex, and particularly race and ethnicity, highlighting the significance of comprehending and addressing disparities and ultimately reducing the disease burden of childhood and adolescent cancer.